Adverse Possession in Thai Law: Principles, Interpretation, and Controversies - temgpongsthorn, wuthichai (Huachiew Chalermprakiet Law Journal, 2025)
This article aims to analyze the legal principles of adverse possession under the Thai legal system, focusing on the provisions of Sections 1382 and 1383 of the Civil and Commercial Code, along with interpretations by the Supreme Court on key elements. It also examines academic debates, particularly regarding the good faith of the possessor—a condition not explicitly required by law but one that significantly affects fairness in practice. The author proposes amending the law to include good faith as a requirement and reevaluating the appropriateness of the prescribed possession period. Additionally, the article suggests preventive measures for landowners, such as regular land inspection, clear demonstrations of ownership intention, and prompt legal action when encroachments are discovered. These measures aim to strike a balance between encouraging land utilization and protecting ownership rights, thereby reducing land-related disputes in Thai society.